KARAKTERISTIK FUNGSI DISTRIBUSI FOUR-PARAMETER GENERALIZED-t - Cahyadi, Rahman; ., Warsono; Usman, Mustofa; Kurniasari, Dian (JURNAL E-DUMATH, 2016)
This research is about the characteristic function of four-parameter generalized tdistribution. Four-parameter generalized t distribution has four parameters whichare Î¼ as a location parameter, Ï as a scale parameter, p and q as a shapeparameter, and B as a function of beta. The characteristic function are retrievedfrom the expectation of e itx , where i as a imaginary number. Then, the characteristicfunction of four-parameter generalized t distribution was able to be determined byusing definition and trigonometric expansions. Based on those two methods thisstudy got the same results and then will be continued proving the fundamentalproperties of the characteristic function of four-parameter generalized t distribution.Furthermore, it needs graph simulation on a characteristic function of four-parameter generalized t distribution. Graph simulation result on the characteristicfunction of four- parameter generalized t distribution was formed a closed curve(circle) are smooth.Keywords: four-parameter generalized t distribution, characteristic function,graph simulation